2022
DOI: 10.3390/su14063526
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Factors Influencing Agritourism Farm Stays and Their Safety during the COVID-19 Pandemic: Evidence from Poland

Abstract: The article presents reasons for the choices and opinions of tourists regarding rest and its safety in agritourism farms in Poland during the COVID-19 pandemic in 2020. We used the diagnostic survey method. We distributed the questionnaire via the Internet on Facebook in thematic groups related to tourism. Facebook respondents were also asked to provide a link to the questionnaire to their tourism-active friends (snowball sampling). We conducted the survey in January 2021. Research has shown that well-educated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…This finding highlights the importance of such features in developing rural tourism to enhance rural community development from multiple perspectives. This finding echoes Zawadka et al (2022); i.e., policymakers should develop rural tourism to provide tourists with a safe and relaxed environment and should not ignore the value of this model for rural tourism.…”
Section: Discussion/implicationsmentioning
confidence: 74%
“…This finding highlights the importance of such features in developing rural tourism to enhance rural community development from multiple perspectives. This finding echoes Zawadka et al (2022); i.e., policymakers should develop rural tourism to provide tourists with a safe and relaxed environment and should not ignore the value of this model for rural tourism.…”
Section: Discussion/implicationsmentioning
confidence: 74%
“…The global spread of the COVID-19 pandemic caused a deep crisis due to the strict preventive measures taken by national governments, causing an immediate economic downturn and, consequently, a severe collapse of tourism demand (Zawadka et al 2022). Almost 58% of the respondents declared that the main cause of the problems in agritourism was COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Spending holidays on agritourism farms depends on many factors and results from a variety of reasons that guide tourists. Recognizing these factors during COVID-19 is particularly important as this allows changes that have occurred in this respect to be identifi ed (Zawadka et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, rural areas attracted slightly less interest from the respondents. Their advantage, as identified in a number of studies, consists of offering a quiet and calm place to stay [75][76][77][78][79][80], which is not necessarily something young people expect from a tourism destination. Also, this is in contradiction with what was observed in a study by Huertas [81], who demonstrated that, during the pandemic, tourists preferred visiting less crowded places in order to avoid physical interaction with other travelers and, thus, to make sure that they kept a suitable distance from people.…”
Section: Reasons For Not Engaging In Tourism Women Menmentioning
confidence: 99%